2019
DOI: 10.1186/s12911-019-0945-2
|View full text |Cite
|
Sign up to set email alerts
|

Smart pumps improve medication safety but increase alert burden in neonatal care

Abstract: BackgroundSmart pumps have been widely adopted but there is limited evidence to understand and support their use in pediatric populations. Our objective was to assess whether smart pumps are effective at reducing medication errors in the neonatal population and determine whether they are a source of alert burden and alert fatigue in an intensive care environment.MethodsUsing smart pump records, over 370,000 infusion starts for continuously infused medications used in neonates and infants hospitalized in a leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…As observed in our studies, minor discrepancies are typically more numerous (Table 4) [10]. Other studies have also noted that medication errors are numerous but are often small and associated with low rates of harm [7,[16][17][18][19]. The risk of calling out these frequent, small discrepancies is an increase in workload and decrease in overall attention.…”
Section: Principal Findingssupporting
confidence: 76%
See 1 more Smart Citation
“…As observed in our studies, minor discrepancies are typically more numerous (Table 4) [10]. Other studies have also noted that medication errors are numerous but are often small and associated with low rates of harm [7,[16][17][18][19]. The risk of calling out these frequent, small discrepancies is an increase in workload and decrease in overall attention.…”
Section: Principal Findingssupporting
confidence: 76%
“…This effect, however, is heavily dependent on user compliance and utilization of specific functionalities vendor products afford, including dose error reduction software [6]. As with EHRs, infusion pump alerts are another source of alert burden and are subject to alert fatigue, which raises a trade-off between potential safety benefits and increased workload for providers [7]. Smart pumps, compared with their analogue counterparts, generate a lot of data to log user interaction with the pumps (eg, pausing of pump infusions and pump alert overrides) and the pump status (eg, infusion start and infusion complete), which are associated with granular timestamps.…”
Section: Introductionmentioning
confidence: 99%
“…They aim to remove the element of human error when setting up infusion pumps. Studies have demonstrated a reduction in programming error rates but with the introduction of new error types—for example, overriding pump warnings and outdated drug libraries 63–67 . A recent NHS funded review of infusion devices recommended that advisory boards of relevant multiprofessional organizations should develop validated national drug libraries for smart infusion pumps 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a reduction in programming error rates but with the introduction of new error types-for example, overriding pump warnings and outdated drug libraries. [63][64][65][66][67] A recent NHS funded review of infusion devices recommended that advisory boards of relevant multiprofessional organizations should develop validated national drug libraries for smart infusion pumps. 68 This could be a positive step in the development of smart pumps and their role in reducing programming errors for PN infusions.…”
Section: Recommendationsmentioning
confidence: 99%
“…In contrast, smart interfaces can improve patient safety and allow clinicians to make more precise, direct, and prompt treatment adjustments and circumvent the need to translate a clearly formed therapeutic intent into an unintuitive sequence of manual programming steps. 2 Furthermore, frequently contacted physical touch controls like buttons and dials on anesthesia monitors and machines 3 can be reservoirs for transmissible nosocomial pathogens. Buttons and dials are difficult to sanitize, and pathogens can prove difficult to eradicate 4 despite precautions such as frequent washing of hands 5 and changing of gloves.…”
mentioning
confidence: 99%